Paruman The Khemion Master: Learning Chemistry Periodic table with Trading Card game - Satrya Mahardhika; Frans Santoso; Nashiruddin Alfath (Journal of Games, Game Art, and Gamification, 2017)
The purpose of this research is to learn about how IP character can help students remembering their lesson. In this case we apply the research to a subject that majority students having difficulty to learn, it is chemistry. Some students say that chemistry is the hardest subject for them. Some say that the hardest part is to remember codes and elements on chemistry. Even they said it is the most boring subject, and usually they get a bad mark for it. Based on our survey, we find out that most of students having difficulties to study the subject using traditional method. They prefer to learn using graphics, because it is easier to remember the codes. For this case, we create a set of play card that can help students remembering the chemicals codes. Each card has a unique IP Character that resembles chemical element. Writers also add an element, which could make the chemistry lesson easier to understand, that is game. A game rule will be applied on the card game, and it will help student learned chemistry. And to make it more attractive and fun, we also try to put some technology to the game. Using a technology called Augment Reality, we try to engage students more.Â